What Motivates People to Earn a Certification in Supply Chain Management? - Silvester Adi Surya Herjuna; Anak Agung Ngurah Perwira Redi (Institute of Computer Science (IOCS), 2022)
This research examines why people enter certification programs. This research examines the supply chain management certification program, the most popular in industry (McCaffery, Backus, & Maxwell, 2020). Extrinsic motivation (Lloyd & Mertens, 2018; Baumann & Bonner, 2016); intrinsic motivation (Quinn et al., 2021; Achtziger & Gollwitzer, 2018; Australian HR Institution, 2017); obtaining a reward or incentive (Australian HR Institution, 2017); and the cost is less than the master's program (Amoruso, 2020; Craig, 2020). AHP is used to rank the 4 criteria's primary aspects. The study sampled experts. Experts are someone with expertise and experience in a subject, system, or sector (Sharma, 2017; Skjong & Wentworth, 2001). This research indicated that incentives were the largest influence in joining a certification program. Extrinsic motivation is second, intrinsic motivation is third, and cost is fourth.